Extracellular vesicles derived from MSCs activates dermal papilla cell in vitro and promotes hair follicle conversion from telogen to anagen in mice. Issue 1 (December 2017) - Rajendran, Ramya; Gangadaran, Prakash; Bak, Soon; Oh, Ji; Kalimuthu, Senthilkumar; Lee, Ho; Baek, Se; Zhu, Liya; Sung, Young; Jeong, Shin; Lee, Sang-Woo; Lee, Jaetae; et al.
Abstract Hair loss is a common medical problem. In this study, we investigated the proliferation, migration, and growth factor expression of human dermal papilla (DP) cells in the presence or absence of treatment with mesenchymal stem cell extracellular vesicles (MSC-EVs). In addition, we tested the efficacy of MSC-EV treatment on hair growth in an animal model. MSC-EV treatment increased DP cell proliferation and migration, and elevated the levels of Bcl-2, phosphorylated Akt and ERK. In addition; DP cells treated with MSC-EVs displayed increased expression and secretion of VEGF and IGF-1. Intradermal injection of MSC-EVs into C57BL/6 mice promoted the conversion from telogen to anagen and increased expression of wnt3a, wnt5a and versican was demonstrated. The first time our results suggest that MSC-EVs have a potential to activate DP cells, prolonged survival, induce growth factor activationin vitro, and promotes hair growthin vivo .